(untitled) (Archives of Mechanics - Test, 1998)
A crystalline solid of C60 (a fullerene) is expected to be an insulator or a semi-conductor. However, one of the most striking properties of C60 - related materials is the observation of relatively high temperature superconductivity in alkali metal doped M3C60 and in various alkaline earth doped compounds. So, the interstitial diffusion of impurities considerably influences the superconductivity phase. The value of the critical temperature below which the superconducting phase exists, strongly depends on many other external influences (electromagnetic, thermal, mechanical, etc.). The paper deals with construction of a phenomenological macroscopic model of interactions between physical fields in fullerenes, basing on the extended thermo-dynamics with internal variables and with the use of Liu’s theorem in order to apply the entropy inequality.